Screening of non-communicable diseases at Dukuh Gerjo Posyandu - Latifah Khusnul Wahyu Utami; Alifia Qudrotul Laila; Dwi Utami (Universitas Muhammadiyah Magelang, 2024)
Lifestyle changes, technological advances, and demographic transitions have triggered an increase in cases of non-communicable diseases (NCDs). Hypertension and diabetes mellitus are two of the most common NCDs and are often associated with other health problems, such as stroke, heart disease, kidney disorders, and death. Therefore, screening and education to improve public understanding and the effectiveness of therapy are crucial. In Padukuhan Gerjo, Grogol Village, Gunung Kidul Regency, an area with a population of about 408 people, including approximately 146 older adults, there is a need to improve access to NCD screening. To support the establishment of a senior health post, community service activities were conducted to screen the health status of local residents, focusing on NCDs. Health checks included measuring blood pressure, random blood sugar (RBS), height and weight, and conducting interviews regarding eating habits. Twenty-eight older adults participated. Health workers from the Grogol Health Center and local health cadres participated to ensure sustainability. The results showed that 55.14% of participants had hypertension; two (7.14%) had hyperglycemia; and approximately 10.71% were obese (BMI ≥25), placing them at high risk of health problems. This initiative will inform future counseling and socialization efforts regarding NCDs among older adults in Padukuhan Gerjo.